Combustion diagnostics of metal particles: a review. (1st April 2023) - Peng, Fan; Liu, Hecong; Cai, Weiwei
Abstract: Metal fuel is one of the attractive alternative fuels for its high energy density and zero carbon emission. In the past, they were often used as additives in fireworks and propellants. More attentions have been paid to metal fuels as the environmental issue and energy dilemma become increasingly severe. Ongoing efforts have been devoted to both modelling and experimental studies of metal fuel combustion. This review mainly focuses on the experimental progress in the combustion of micron-scale metal fuels during the past three decades. The experimental setups and the combustion diagnostics techniques used for single particle combustion and metal dust flames have significant distinctions, so they have been summarized separately. Those setups to produce single particle flames or metal dust flames are discussed in terms of their structure, scope of application, advantages and disadvantages. The diagnostics techniques are classified according to the physical parameters that are commonly adopted to characterize the metal particle combustion including burn time, temperature, particle size, dust concentration and burning velocity. Both online and offline measurement techniques are investigated in detail focusing on the measurement principle, system configuration and uncertainty analysis. Finally, the review is concluded with some unresolved problems in the field of metal particle combustion diagnostics, and provides insights into promising future research directions.